2015
DOI: 10.1007/s10147-015-0823-6
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of palonosetron and 1-day dexamethasone in moderately emetogenic chemotherapy compared with fosaprepitant, granisetron, and dexamethasone: a prospective randomized crossover study

Abstract: PALO and 1-day DEX is almost equivalent to FAPR, GRAN, and DEX for MEC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 18 publications
0
16
0
Order By: Relevance
“…We identified 1,613 records about CINV through database searching and focused on 61 potentially relevant randomized control trials with olanzapine‐based triple regimens or NK‐1RAs‐base triple regimens in the experimental arm. However, 18 trials were not eligible for the following reasons: associating with MEC , using nonstandard triple CINV regimens , unavailable measured outcomes , carboplatin area under the curve remain unclear , and using quadruplex antiemetic regimens in the experimental arm . We finally included 42 trials focused on HEC involving 16,609 cancer patients using olanzapine‐based triple regimens (olanzapine + 5‐HT 3 RA + dexamethasone, n = 657), NK‐1Ras‐based triple regimens (NK‐1RAs + 5‐HT 3 RA + dexamethasone, n = 10,510), or conventional duplex control regimens (5‐HT 3 RA + dexamethasone, n = 5,442) to control CINV in this network meta‐analysis.…”
Section: Resultsmentioning
confidence: 99%
“…We identified 1,613 records about CINV through database searching and focused on 61 potentially relevant randomized control trials with olanzapine‐based triple regimens or NK‐1RAs‐base triple regimens in the experimental arm. However, 18 trials were not eligible for the following reasons: associating with MEC , using nonstandard triple CINV regimens , unavailable measured outcomes , carboplatin area under the curve remain unclear , and using quadruplex antiemetic regimens in the experimental arm . We finally included 42 trials focused on HEC involving 16,609 cancer patients using olanzapine‐based triple regimens (olanzapine + 5‐HT 3 RA + dexamethasone, n = 657), NK‐1Ras‐based triple regimens (NK‐1RAs + 5‐HT 3 RA + dexamethasone, n = 10,510), or conventional duplex control regimens (5‐HT 3 RA + dexamethasone, n = 5,442) to control CINV in this network meta‐analysis.…”
Section: Resultsmentioning
confidence: 99%
“…Regarding vomiting, a study comparing two-drug (palonosetron+DEX) and three-drug combinations (NK1RA + first-generation 5HT3RA + DEX) for an L-OHP-based regimen showed the rates of no vomiting in the acute and delayed phases to be 99.4 and 95.5%, respectively, with the 2-drug combination [28]. Our rates of no vomiting in the acute and delayed phases in the two-drug group (palonosetron+DEX) were 95.9 and 96.9%, respectively, which were almost the same as in that previous study.…”
Section: Discussionmentioning
confidence: 99%
“…Randomized controlled trials in patients receiving MEC are summarized in Table 6 . 38 , 70 72 , 74 82 About half the MEC trials tabulated reported no significant improvements in nausea control in any CINV phase with the addition of an NK 1 RA to a two-drug antiemetic regimen. Of those that did report a significant improvement in nausea control in any phase, 70 72 , 75 , 76 , 79 , 80 none showed significant improvements in nausea control across the acute, delayed, and overall phases.…”
Section: Pharmacokinetic Receptor Occupancy and Pharmacodynamic Promentioning
confidence: 99%